Antibacterial Properties of Essential Oil (EO) Extracted from Nigella sativa Linn. (Black cumin) and its Application Against Vibrio cholerae in Ground Chicken Meat - Deloer, Sharmina; Bari, ML; Hoque, Md Mahfuzul (Bangladesh Journal of Microbiology, 2019)
Chemical preservatives for food preservation at high concentration are hazardous for public health. The natural antimicrobials from plants, herbs and spices have been given priority as alternatives of the chemical preservatives. In this study, antibacterial activity of the essential oil (3%) from black cumin seeds was tested against five food borne pathogens viz Staphylococcus aureus (ATCC 25923), Shigella dysenteriae-I (MJ-84), Escherichia coli 0157:H7 (ATCC 12079), Escherichia coli (ATCC 25922) and Vibrio cholerae( ATCC 6395) using disc diffusion method. The essential oil (EO) showed antibacterial activity against both Gram positive and Gram negative bacteria with the highest inhibition against S. aureus (17.4 ± 0.2) and the lowest against Vibrio cholerae (14.5 ± 1.0). No activity was observed against E. coli and E. coli O157:H7. The effect of temperature and pH on the antibacterial activity of the EO from black cumin seeds was determined. At 100°C for 30 min treatment, no significant reduction of antibacterial activity of the EO was observed, suggesting that high temperature does not affect the activity. The optimum temperature for the activity was recorded at 50°C. The EO showed the highest activity at pH 7.0 (optimum) with an insignificant change of activity at pH 5.0, 9.0 and 10.0. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of EO against S. aureus, V. cholerae and Shigella dysenterae were determined by two fold dilution method at optimum temperature of 50°C and 37oC and optimum pH at 7.0 and 5.0, respectively, which ranged from 0.125 (S. aureus) to 1.0% (Shigella dysenterae), with the MBC of 0.25 to 2.0%, respectively. Three times of MIC value of EO (1.5%) was applied in ground chicken meat seeded with V. cholerae ATCC 6395 and was kept at -20°C for 10 days. The test organism was diminished within 24 hours, suggesting that the EO from black cumin is highly active in vivo and could be used as preservative in ground chicken meat. The results of this study provide new dimension of research on EOs from spices against foodborne pathogens in vivo in controlling their growth in meat based food and food products. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 55-60